Biofuels Challenges and opportunities - Al Qubeissi, Mansour (IntechOpen, 2019)
Amongst concerns about climate change, energy security decline and depletion of fossil fuels, this book explores the high importance of and interests in alternative energy resources. Many studies have shown that biomass fuels are sustainable, environmentally friendly and can be the most appropriate replacement to the depleting crude oil. Additionally, they can expand green landscapes, create new job opportunities, be directly utilised in standard power systems and improve combustion performance. Biomass fuels can be limited due to production cost and competition with food. Therefore, plant and food wastes play an important role in reducing these costs and recycling dump bio-materials. Production of biofuels from non-food biomass has emerged as a sustainable option to tackle the problems associated with growing demands for energy.